2023
DOI: 10.1063/5.0160347
|View full text |Cite
|
Sign up to set email alerts
|

Study on cavitating vortex rope characteristics of reversible pump-turbine under part load turbine condition

Shujiao Pang,
Baoshan Zhu,
Yunde Shen
et al.

Abstract: Pressure fluctuations in the draft tube mainly arise from the rotational motion of the vortex rope. The formation and development of the vortex rope are significantly influenced by cavitation. However, the precise mechanism underlying the progression of cavitation from its initial weak state to a more severe level remains unclear. The objective of this study is to investigate cavitation in a pump-turbine operating under part load turbine conditions. Numerical simulations were conducted to analyze the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The equations of SST are shown in Equations ( 5) and ( 6). This model provides better predictions of flow separation under reverse pressure gradients and is widely used in the calculation of pump turbines [26][27][28][29][30]. In this study, the SST turbulence model is selected for the CFD calculation.…”
Section: Methodsmentioning
confidence: 99%
“…The equations of SST are shown in Equations ( 5) and ( 6). This model provides better predictions of flow separation under reverse pressure gradients and is widely used in the calculation of pump turbines [26][27][28][29][30]. In this study, the SST turbulence model is selected for the CFD calculation.…”
Section: Methodsmentioning
confidence: 99%
“…The study by Lin et al [15] showed that the draft tube vortex rope is also significantly affected by leakage flow and the blade vortex. Pang et al studied the influence of the cavitation number on the draft tube vortex rope [16]. Numerical simulation revealed that, under different cavitation numbers, the vortex rope presents a spiral shape or a torch-like shape, and the torch-like vortex rope under a lower cavitation number has a higher swirling intensity and a lower dominant frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [14] studied the energy characteristics of the pump turbine, analyzing the hydraulic losses of different internal structures quantitatively under various load conditions. Pang et al [15] summarized the variations in the energy characteristics of the vortex rope's evolution and examined the hydraulic characteristics of the pump turbine. Abu Shahzer et al [16] investigated the pump turbine operating at different cavitation numbers and proposed a method to effectively suppress the generation of the vortex rope.…”
Section: Introductionmentioning
confidence: 99%